2008
DOI: 10.1111/j.1365-2934.2007.00828.x
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the turnover issue among new nurses from a generational viewpoint

Abstract: Nurse Managers must offer Nexters, from the beginning of their career, a meaningful work and supportive environment. Without the efforts of the organization to improve the work environment and support nurses, this generation may not feel valued and move to another organization that will support them or another career that will offer fulfilment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
142
0
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(159 citation statements)
references
References 44 publications
(51 reference statements)
12
142
0
5
Order By: Relevance
“…This reflects the importance of coworker support as indicated by previous studies 7,19,35) . Suzuki et al (2006) reported a risk ratio of 2.29 (p<0.01) times greater turnover for NGNs who indicated a lack of social support from peers 7) .…”
Section: Job Stressorsmentioning
confidence: 82%
See 2 more Smart Citations
“…This reflects the importance of coworker support as indicated by previous studies 7,19,35) . Suzuki et al (2006) reported a risk ratio of 2.29 (p<0.01) times greater turnover for NGNs who indicated a lack of social support from peers 7) .…”
Section: Job Stressorsmentioning
confidence: 82%
“…It has been indicated that supervisors' management style and attitude may influence the level of support provided to NGNs and that these have an effect on their rate of resignation 4,10,19,35,40) . Since there is also an indication that consideration on the part of managers directly and positively affects the retention of staff nurses 40) , hospital employers and managers need to understand how to exhibit a beneficial management style for the prevention of NGNs' early resignation.…”
Section: Job Stressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings are consistent with the Quebec, Canada, which revealed that 61.5% intended to quit their present job for another job while 25.6% will remain in their profession and 12.9%, reported considering leaving the profession. [15] The reported choice of leaving the country is a dangerous indicator among Palestinians in Gaza. This could be also contributed to other life stressors such as the unstable political situation, siege, blockade and un-safe life related to bombardment especially in the last war at the end of year 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Nem találtunk számottevő kapcsolatot a munkahelyi stressz-szint pályaelhagyási és migrációs magatartást befolyásoló hatásában, így eredményeink a más egészségügyi szakdolgozók körében készült, ugyanezen kérdőív segítségével mért munkahelyi stressz-szint migrációs és pályaelhagyási magatartást befolyásoló hatásá-nak vizsgálata során keletkezett eredményekhez képest eltérést mutatott. Ennek hátterében az állhat, hogy a felhasznált szakirodalmakban a részt vevők jelentős része ápoló volt, így heterogén az iskolai végzettségük, munkavégzésük (három műszak, 12 órás napi beosztás), valamint az ebből fakadó számos betöltött munkahelyi pozíció (segédápoló, szakápoló, osztályvezető, intéz-ményvezető ápoló) eltérő [16][17][18]. Mintánkban elenyé-sző csoport fejezte ki elégedettségét a munkáltatója anyagi megbecsülésével kapcsolatban (6,5%).…”
Section: Eredeti Közleményunclassified